Community and Teacher Education, Convergence or Divergence? Saskatoon and the Saskatoon Normal School, 1930–1950 - Lemisko, Lynn Ellen; Porter, Gemma; Clausen, Kurt (Alberta Journal of Educational Research, 2021)
Teacher education in Canada is a contested discipline with long standing national and international debates about what teachers need to know and be able to do. But teacher education programmes are also influenced by the social, political, and economic context in which the programmes developed, so it is reasonable to suppose that debates about teacher education programming are connected to local issues and concerns of the community. Given the supposition that teacher education programming is shaped, at least in part, by the tensions and contentions arising in particular localities, this study provides historical insight into the relationship between a local community and a teacher education program by examining connections between the Saskatoon Normal School teacher education program and the community of Saskatoon in the years of 1930–1950. Key words: history of teacher education; community and teacher education La formation des enseignants au Canada est une discipline contestée qui fait l'objet de débats nationaux et internationaux de longue date sur ce que les enseignants doivent savoir et être capables de faire. Mais les programmes de formation des enseignants sont également influencés par le contexte social, politique et économique dans lequel ils ont été élaborés. Il est donc raisonnable de supposer que les débats sur les programmes de formation des enseignants sont liés aux questions et préoccupations locales de la communauté. Étant donné l'hypothèse selon laquelle les programmes de formation des enseignants sont façonnés, du moins en partie, par les tensions et les différends qui surgissent dans des localités particulières, cette étude fournit un aperçu historique de la relation entre une communauté locale et un programme de formation des enseignants en examinant les liens entre le programme de formation des enseignants de la Saskatoon Normal School et la communauté de Saskatoon dans les années 1930-1950. Mots clés: histoire de la formation des enseignants; communauté et formation des enseignants